Archaeological Fish Bones Online: a digital archive of Sydney fishes - Sarah Colley; Rowan Brownlee (Internet Archaeology, 2010)
The article presents the Archaeological Fish Bone Images sustainable digital archive and XTF-based image search and presentation tools developed with University of Sydney Library. The archive contains over 500 images of modern and archaeological fish remains and was developed as part of an archaeological research project into colonial and traditional Aboriginal fishing practices in Sydney, New South Wales, Australia from c.3000 years ago to the late 19th century. Links are provided to research information about fish ecology and fishing, the cultural and historical significance of fish taxa and details of taxonomic and anatomical nomenclature.